A Death in the Family: Report of a Single-Session Trauma Group for Nursing Home Residents and Staff. Issue 3 (3rd July 2018) - Schramm, Marc G.
ABSTRACT: This article describes a single-session trauma-debriefing group conducted at a nursing home following the death of a resident on an outing. The group had as its core an existing weekly therapy group in the facility, with the addition of affected staff, family, and other residents who were on the outing. The treatment illustrates four principles relevant to counseling and psychotherapy in nursing homes: 1) recognition of death; 2) treatment in and of the milieu; 3) flexibility and structure; and 4) dealing with countertransference. Along the way, we see how the residents are capable of giving, and not merely receiving.